Radiographic evaluation of periradicular repair after endodontic treatment of dog's teeth with induced periradicular periodontitis - Grecca, Fabiana Soares; Leonardo, Mario Roberto [UNESP]; Silva, Léa Assed Bezerra da; Tanomaru Filho, Mario [UNESP]; Borges, Marco Aurelio Gagliardi [UNESP] (Wolters Kluwer, 2001)
Eighty-four root canals of premolars from six dogs were left open for 7 days, and then sealed and followed for 45 days until periradicular periodontitis developed. The root canals were then treated endodontically using 5.25% sodium hypochlorite as the irrigating solution. After instrumentation, all root canals were filled with a calcium hydroxide-based antibacterial dressing (Calen PMCC or Calasept) that was left in place for 30 days. After this period the root canals were filled with gutta-percha cones and a root canal sealer (Sealapex or AH Plus)-group I: Calen PMCC + Sealapex; group II: Calasept + Sealapex; group III: Calen PMCC + AH Plus; and group IV: Calasept + AH Plus. Periapical radiographs of the teeth were made after root canal filling and after 90, 180, 270, and 360 days. Radiographic images were digitalized by scanning, and the Mocha program was used to measure the periapical lesions. Analysis showed that the lesions of groups I to III were statistically similar reduction in size, whereas group IV had a smaller reduction in lesion size (p < 0.05). Copyright © 2001 by The American Association of Endodontists.
Keywords: AH Plus; biomedical and dental materials; calcium hydroxide; calen; epoxy resin; root canal filling material; salicylic acid derivative; sealapex; animal; comparative study; dog; drug combination; endodontics; methodology; radiography; tooth periapical disease; Animals; Calcium Hydroxide; Dogs; Drug Combinations; Epoxy Resins; Periapical Periodontitis; Root Canal Filling Materials; Root Canal Irrigants; Root Canal Therapy; Salicylates